2015
DOI: 10.2196/jmir.4329
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Adolescent Positive Psychology Program in Schools: Randomized Controlled Trial

Abstract: BackgroundAdolescent mental health is characterized by relatively high rates of psychiatric disorders and low levels of help-seeking behaviors. Existing mental health programs aimed at addressing these issues in adolescents have repeated inconsistent results. Such programs have generally been based on techniques derived from cognitive behavioral therapy, which may not be ideally suited to early intervention among adolescent samples. Positive psychology, which seeks to improve well-being rather than alleviate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 33 publications
1
47
0
2
Order By: Relevance
“…The lack of effect on MHC-SF well-being scores observed in this intervention are comparable with results from similar Web-based intervention trials, conducted in older (mean age 43.2 years) [25] and under 16-years-old school-based samples [26]. Across both studies, positive benefits were shown in depression scales but benefits assessed using mental well-being scales themselves were minuscule and nonsignificant both immediately after the intervention and at follow-up.…”
Section: Discussionsupporting
confidence: 79%
“…The lack of effect on MHC-SF well-being scores observed in this intervention are comparable with results from similar Web-based intervention trials, conducted in older (mean age 43.2 years) [25] and under 16-years-old school-based samples [26]. Across both studies, positive benefits were shown in depression scales but benefits assessed using mental well-being scales themselves were minuscule and nonsignificant both immediately after the intervention and at follow-up.…”
Section: Discussionsupporting
confidence: 79%
“…Generally, there is evidence that engagement is predictive of intervention success. 8 , 24 - 27 For example, Glen and colleagues 28 could prove that higher engagement of patients treated for anxiety disorder with cognitive behavior therapy was associated with better outcomes.…”
Section: Intervention Engagement As a Moderatormentioning
confidence: 99%
“…Of the 264 participants in our study, 74 completed the intervention. When comparing our findings with the literature, we found that, in fact, there is greater adherence to face-to-face therapies (19)(20)(21)(22)(30)(31) and that most studies that tested interventions to improve mental health over the Internet presented significant losses during the process, ranging from 44.1% to 81.63% (32)(33)(34)(35) .…”
Section: Discussionmentioning
confidence: 57%